2009
DOI: 10.1038/nm.2010
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Wnt–β-catenin signaling disrupts adult renal homeostasis and leads to cystic kidney ciliopathy

Abstract: Cystic kidney disease represents a major cause of end-stage renal disease, yet the molecular mechanisms of pathogenesis remain largely unclear. Recent emphasis has been placed on a potential role for canonical Wnt signaling, but investigation of this pathway in adult renal homeostasis is lacking. Here we provide evidence of a previously unidentified canonical Wnt activity in adult mammalian kidney homeostasis, the loss of which leads to cystic kidney disease. Loss of the Jouberin (Jbn) protein in mouse leads t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
171
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(183 citation statements)
references
References 58 publications
11
171
1
Order By: Relevance
“…11 Downregulation of Wnt/b-catenin activities and cystic kidney ciliopathy are observed in the KO mice of Ahi1 that encodes a cilial protein Jouberin and may be genetically interactive with Lrp6 in polycystic kidney disease (PKD) and related cystogenesis. 29 In support of this, a recent study revealed that LRP5 mutations and canonical Wnt signaling are associated with hepatic cystogenesis. 30 However, Wnt/ b-catenin signaling is not involved in renal cystic formation of the mutant mice of Invs that encodes a cilial protein inversin or nephrocystin-2.…”
Section: Lrp6-mediated Wnt/b-catenin Signaling In Renal Development Amentioning
confidence: 86%
“…11 Downregulation of Wnt/b-catenin activities and cystic kidney ciliopathy are observed in the KO mice of Ahi1 that encodes a cilial protein Jouberin and may be genetically interactive with Lrp6 in polycystic kidney disease (PKD) and related cystogenesis. 29 In support of this, a recent study revealed that LRP5 mutations and canonical Wnt signaling are associated with hepatic cystogenesis. 30 However, Wnt/ b-catenin signaling is not involved in renal cystic formation of the mutant mice of Invs that encodes a cilial protein inversin or nephrocystin-2.…”
Section: Lrp6-mediated Wnt/b-catenin Signaling In Renal Development Amentioning
confidence: 86%
“…adenomatous polyposis coli, Apc; van gogh-like 2, Vangl2; and -catenin) have been localized to the cilium (Corbit et al, 2008;Ross et al, 2005). Loss of ciliary and basal body proteins results in dysregulation of -catenin signaling (Corbit et al, 2008; Gerdes et al, 2007;Lancaster et al, 2011a;Lancaster et al, 2011b), with concomitant defects in non-canonical signaling (impaired convergent extension movements, neural tube closure failure and disorganization of stereocilia in the mouse inner ear), highlighting an emerging role for the basal body and primary cilium in Wnt/PCP signaling (Ferrante et al, 2009; Gerdes et al, 2007; Hunkapiller et al, 2010;Lancaster et al, 2009;McDermott et al, 2010;Simons et al, 2005).…”
Section: Wnt Signalingmentioning
confidence: 99%
“…adenomatous polyposis coli, Apc; van gogh-like 2, Vangl2; and -catenin) have been localized to the cilium (Corbit et al, 2008;Ross et al, 2005). Loss of ciliary and basal body proteins results in dysregulation of -catenin signaling (Corbit et al, 2008; Gerdes et al, 2007;Lancaster et al, 2011a;Lancaster et al, 2011b), with concomitant defects in non-canonical signaling (impaired convergent extension movements, neural tube closure failure and disorganization of stereocilia in the mouse inner ear), highlighting an emerging role for the basal body and primary cilium in Wnt/PCP signaling (Ferrante et al, 2009; Gerdes et al, 2007; Hunkapiller et al, 2010;Lancaster et al, 2009;McDermott et al, 2010;Simons et al, 2005).The physiological relevance of dysregulated Wnt/PCP signaling is evident in the development and function of several vertebrate organs, such as kidney, cochlea and neural tube. By patterning the planar surface of an epithelium or tissue, PCP proteins, such as disheveled 1 (Dvl1), Dvl2 and Dvl3, can regulate the apical movement of basal bodies from deep within the cytoplasm to the cell surface and, thus, cilia formation and positioning in the Xenopus mucociliary epithelia (Park et al, 2008).…”
mentioning
confidence: 99%
“…2A). However, upon canonical Wnt activation, Jbn is released from the cilia via retrograde IFT, which then physically interacts with β-catenin to facilitate its translocalization to the nucleus and activation of β-catenin-dependent transcription of target genes 65,66 (Fig. 2B).…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%